2021
DOI: 10.5194/essd-13-1957-2021
|View full text |Cite
|
Sign up to set email alerts
|

Complementing regional moment magnitudes to GCMT: a perspective from the rebuilt International Seismological Centre Bulletin

Abstract: Abstract. Seismologists and geoscientists often need earthquake catalogues for various types of research. This input usually contains basic earthquake parameters such as location (longitude, latitude, depth, and origin time), as well as magnitude information. For the latter, the moment magnitude Mw has become the most sought after magnitude scale in the seismological community to characterize the size of an earthquake. In this contribution we provide an informative account of the Mw content for the newly rebui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 66 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The original M w values reported from sources 1 to 3 in the list above were used for the corresponding earthquakes. For those with locations provided by ISC (sources 4 and 5), M w was used if reported, preferably from the Global CMT catalogue (Dziewonski et al, 1981;Ekström et al, 2012) or alternatively from other agencies as reported by ISC (Di Giacomo et al, 2021). If no M w was available, we adopted the hierarchy proposed by ISC for selecting the most reliable, preferred magnitude type (Text S4, Di Giacomo and Storchak, 2016).…”
Section: Earthquake Cataloguementioning
confidence: 99%
“…The original M w values reported from sources 1 to 3 in the list above were used for the corresponding earthquakes. For those with locations provided by ISC (sources 4 and 5), M w was used if reported, preferably from the Global CMT catalogue (Dziewonski et al, 1981;Ekström et al, 2012) or alternatively from other agencies as reported by ISC (Di Giacomo et al, 2021). If no M w was available, we adopted the hierarchy proposed by ISC for selecting the most reliable, preferred magnitude type (Text S4, Di Giacomo and Storchak, 2016).…”
Section: Earthquake Cataloguementioning
confidence: 99%
“…We aim to narrow the gap between different disciplines in Earth science, enlarging the observation systems of natural processes to improve forecast, and encourage innovation in scientific and technological responses towards a more sustainable environment. The open source computational infrastructure presented here together with complementary initiatives of open data (e.g., García-Mayordomo et al, 2012;DeFelipe et al, 2021;Di Giacomo et al, 2021;Zahorec et al, 2021), will reinforce the understanding of the evolution of the Earth system to improve the predictability of future scenarios. Finally, we want to contribute to a harmonized strategy for software sharing in Earth science, making accessible tools that will help develop comprehensive digital twins of the Earth system in the future.…”
Section: Introductionmentioning
confidence: 99%